THE DYNAMICS OF ILLEGAL STONE MINING CONFLICT IN THE KENDENG MOUNTAINS, SUKOLILO SUBDISTRICT - Estiyana Indriyani; Teguh Yuwono; Kismartini (SOSIOEDUKASI, 2026)
Rock mining resources in the Kendeng Mountains, Sukolilo District, still face several problems in their management process, particularly the widespread presence of illegal miners operating without permits and the conflicts arising from environmental damage around the mining areas. This study aims to examine the government’s supervision system in addressing rock mining problems in the Kendeng Mountains as well as the dynamics of conflict between miners and the surrounding community. The research employed a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation using purposive sampling involving local communities, miners, village officials, local government representatives, and law enforcement officers. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification. The findings indicate that the rock mining conflict in the Kendeng Mountains is multidimensional, encompassing regulatory conflicts, technical-operational conflicts, and community resistance caused by environmental degradation, dust pollution, road infrastructure damage, and declining agricultural productivity. The increasing number of illegal mining activities has triggered horizontal conflicts between miners and local residents, as well as vertical conflicts between miners and the government due to discrepancies between formal regulations and practices in the field. Government supervision and conflict prevention efforts have not been implemented optimally and have not yet fostered a sense of responsibility among miners, which is influenced by weak field supervision, limited understanding of licensing procedures among miners, and insufficient policy socialization. Therefore, this study emphasizes the importance of strengthening the supervision system, enforcing stricter law enforcement, enhancing community participation, and fostering collaboration among stakeholders to achieve sustainable natural resource management and to minimize mining conflicts in the Kendeng Mountains, Sukolilo District.